1998
DOI: 10.1046/j.1365-2443.1998.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Axin, an inhibitor of the Wnt signalling pathway, interacts with β‐catenin, GSK‐3β and APC and reduces the β‐catenin level

Abstract: Background: The Wnt/Wingless signalling pathway plays an important role in both embryonic development and tumorigenesis. b-Catenin and Axin are positive and negative effectors of the Wnt signalling pathway, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
213
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(220 citation statements)
references
References 46 publications
6
213
0
1
Order By: Relevance
“…Therefore, we investigated whether axin polymerization and puncta formation were required for assembly of the destruction complex, and whether they influence recruitment and b-catenin degradation. Previous studies have shown that the DIX domain is important for b-catenin regulation (Kishida et al, 1999;Sakanaka and Williams, 1999), however, it has also been reported that deletion of the DIX domain does not affect the ability of axin to alter b-catenin localization (Nakamura et al, 1998). We tested the ability of axinDDIX-RFP to recruit b-catenin in cells treated with proteasome inhibitors ( Figure 6).…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, we investigated whether axin polymerization and puncta formation were required for assembly of the destruction complex, and whether they influence recruitment and b-catenin degradation. Previous studies have shown that the DIX domain is important for b-catenin regulation (Kishida et al, 1999;Sakanaka and Williams, 1999), however, it has also been reported that deletion of the DIX domain does not affect the ability of axin to alter b-catenin localization (Nakamura et al, 1998). We tested the ability of axinDDIX-RFP to recruit b-catenin in cells treated with proteasome inhibitors ( Figure 6).…”
Section: Resultsmentioning
confidence: 96%
“…The APC gene encodes a protein of 2843 amino acids that are associated with b-catenin, Axin and conductin/Axil (Rubinfeld et al, 1993;Behrens et al, 1998;Ikeda et al, 1998Nakamura et al, 1998;Yamamoto et al, 1998). These proteins are important components of the Wnt/ Wingless signal transduction pathway, which controls embryonic pattern formation (Nusse and Varmus, 1992;Cadigan and Nusse, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The product of AXIN1, a gene that was first isolated from the murine Fused locus as an inhibitor of Wnt signaling (Zeng et al 1997), was later shown to reduce -catenin by forming a complex with -catenin, GSK-3 (glycogen synthase kinase-3 ), and APC (adenomatous polyposis coli) (Kishida et al 1998, Nakamura et al 1998. By screening primary HCCs for mutations in the human homologue (AXIN1), we previously identified somatic mutations that all resulted in truncation of the predicted protein (Satoh et al 2000).…”
Section: Introductionmentioning
confidence: 99%